Compliant Compression Reconstruction of the Proximal Femur Is Durable Despite Minimal Bone Formation in the Compression Segment. Issue 7 (17th February 2021) - Christ, Alexander B.; Fujiwara, Tomohiro; Fabbri, Nicola; Healey, John H.
Abstract: Background: Compliant compression fixation was developed to promote permanent bone-prosthesis osteointegration while preserving bone stock in patients needing endoprosthetic reconstructions. This has demonstrated durability in the distal femur, with reliable cortical hypertrophy adjacent to the implant. However, the extent of bone formation and prosthetic survivorship of proximal femoral replacements with compliant compression fixation has not been established. Questions/purposes: (1) How much bone formation occurs across the compression segment in patients treated with a proximal femoral replacement implant using compliant compression fixation? (2) What were the Musculoskeletal Tumor Society (MSTS) scores at minimum 24-month follow-up of patients who received this reconstruction? (3) What is the implant survivorship free from implant removal or revision for any reason at final follow-up? Methods: From 2006 to 2018, we performed 213 proximal femoral replacements in patients with oncologic conditions of the proximal femur where the trochanters could not be preserved. Of these, 6% (12 of 213) were performed with an implant that used compliant compression fixation. We used this device in primary oncologic reconstructions in patients younger than 65 years of age without metastases who had nonirradiated bone with the requisite ≥ 2.5 mm of cortical thickness in the hope that it would provide more durable fixation and bone stock preservation than conventional reconstructions. All patients were followed for longer than 2 years except one who died in that interval. Median (range) follow-up was 6 years (2 to 10 years). Seven patients received diagnosis-specific chemotherapy in a consistent manner based on Children's Oncology Group chemotherapy protocols. Using the NIH-developed ImageJ open-access software, we measured the area of bone under compression on 3-, 6-, 9-, 12-, 18-, and 24-month radiographs and the length of the traction bar potential-compression distance, reconciling independent measures from two investigators using the identical method as published for the distal femur with compression fixation. The duration of prosthesis retention was evaluated using a competing risk analysis for the 11 surviving patients. Results: Bone hypertrophy in the compression segment was scant. At the final analysis, cortical bone formation was a median (range) of 4 (-7 to 14) above baseline. The median (range) MSTS score was 27 (19 to 30). One implant failed after trauma, and the patient underwent revision of the implant. Conclusion: Despite scant bone formation across the compression segment and drastically less formation than reported for distal femoral replacements, compliant compression fixation of the proximal femur demonstrated good survivorship in patients 65 years or younger with localized sarcoma and nonirradiated, adequate bone stock in this small, retrospective series. Patients achieved good functional outcomes at final follow-up. The potential benefit of this reconstruction method should be weighed against the initial period of limited weightbearing and the life expectancy of the patient. Level of Evidence: Level IV, cohort study.